2015
DOI: 10.1016/j.amepre.2015.01.013
|View full text |Cite|
|
Sign up to set email alerts
|

Change in Neighborhood Socioeconomic Status and Weight Gain

Abstract: Introduction Despite a proposed connection between neighborhood environment and obesity, few longitudinal studies have examined the relationship between change in neighborhood socioeconomic deprivation, as defined by moving between neighborhoods, and change in body weight. The purpose of this study is to examine the longitudinal relationship between moving to more socioeconomically deprived neighborhoods and weight gain as a cardiovascular risk factor. Methods Weight (kg) was measured in the Dallas Heart Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 45 publications
0
59
2
Order By: Relevance
“…514,17 However, this does not support our findings for cluster 6. Cluster 6 had a low percentage of people living below the poverty line, unemployed, and Black.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…514,17 However, this does not support our findings for cluster 6. Cluster 6 had a low percentage of people living below the poverty line, unemployed, and Black.…”
Section: Discussioncontrasting
confidence: 99%
“…Seven categories (education, wealth, income, race, employment, housing, and land-use), defined by 12 variables from the Census (Table 1) and cited in previous work on neighborhood-level SES and health, were identified as being influential. 6,7,11,12,14,21,25,32,33 These variables were chosen without previous knowledge of their distribution across our study area, and no variables were excluded in a sensitivity analysis to try to determine the most influential attributes or bias the results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neighborhood deprivation, consistently associated with mortality (Pearson, Apparicio, & Riva, 2013; Ross, Oliver, & Villeneuve, 2013), is one such factor. Research has consistently found effects of neighborhood deprivation on BMI (El-Sayed, Scarborough, & Galea, 2012; Matheson, Moineddin, & Glazier, 2008; Powell-Wiley et al, 2015), And neighborhood SES has also been associated with obesity risk (Black & Macinko, 2008; El-Sayed et al, 2012; Glass, Rasmussen, & Schwartz, 2006). Macro-level social factors such as neighborhood-level socioeconomic deprivation are becoming increasingly relevant to research investigating environmental determinants of health.…”
mentioning
confidence: 99%